Marketingový mix nové pobočky společnosti Fabricland - Směřičková, Michaela (Vysoké učení technické v Brně. Fakulta podnikatelská, 2018)
Předmětem diplomové práce marketingový mix nové pobočky společnosti Fabricland je analýza současného stavu marketingového mixu vybraného podniku a sestavení doporučení pro její vylepšení. Teoretické východisko se zaměřuje na vymezení teoretických poznatků marketingu. Druhá část je věnována analýze současného stavu ve společnosti. V poslední části budou poskytnuty návrhy pro optimalizaci marketingového mixu společnosti.

The subject matter of this dissertation, marketing mix for a new branch for the company Fabricland is to analyze the current condition of the company’s marketing mix and to put together recommendations for its improvement. The theoretical part focuses on defining theoretical knowledge of marketing. The second part is dedicated to analyzing the current condition of the company. The last part will provide proposals for optimization for the company’s marketing mix.
Marketing Mix for a new Branch for the Company Fabricland
Keywords: marketing; marketingový mix; produkt; cena; distribuce; propagace; služba; konkurence; marketing; marketing mix; product; price; promotion; distribution; service; competition